LEADER COMMUNICATION STYLE AND WILLINGNESS TO WORK: SYSTEMATIC LITERATURE REVIEW - Mercidominick Fidelius Conrad Menachem Purba; Evi Thelia Sari (Universitas Ciputra Surabaya, 2025)
This study aims to evaluate the relationship between communication styles adopted by leaders and employee work ethic levels, using a systematic literature review (SLR) approach. In contemporary organizational dynamics, the role of leadership communication effectiveness has become crucial foundations in determining performance quality, motivation levels, and the extent to which employees are actively engaged in their work. Although numerous previous studies have addressed the relationship between leadership and motivational aspects and employee performance, in-depth exploration of the influence of leader communication styles on work ethics remains limited. Therefore, this study aims to systematically map the literature to identify discourse patterns, thematic trends, and research gaps with potential for future development in the future. The study subjects included scientific articles published in reputable journals, both national and international, between 2018 and 2025. The article selection process employed strict inclusion and exclusion criteria, with an emphasis on topics related to leadership, organizational communication, work culture, motivation, and human resource performance. For data analysis, VOSviewer software was used with bibliometric methods, including density visualization, network visualization techniques. This analysis provides a basis for researcher to identify the most prominent keywords, construct interrelated thematic clusters, and observe changes in research trends over period. The main findings of this analysis revealed that the terms employee performance and work motivation were the two most frequently encountered keywords, reflecting the dominance of these two topics in the relevant academic literature. Three main clusters were formed: a green cluster focusing on motivation and performance, a red cluster addressing organizational commitment, work culture, and internal communication, and a blue cluster reflecting studies on leadership styles. The overlay visualization results indicate a shift in the study’s focus toward employee engagement, internal communication, and transformational leadership in a digital context. This demonstrates that a leader’s communication style has a broad impact, encompassing performance, emotional engagement, organizational culture, and psychological well – being. Thus, leadership communication is a strategic element linking employee motivation, culture, engagement, and performance. These findings also open up opportunities for further research, particularly in the context of digital organizations, multicultural work environments, and mental health issues in the workplace.